Atribut Kinerja Pelayanan Dalam Mempengaruhi Masyarakat Kota Medan Memilih Perusahaan Asuransi - Hazmanan Khair Pasaribu (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Among the reason of choosen assurannce company, performance service is the mostly affected. So that this research aims to find affect of performance service to consumen decision about assurance company. The result showed that performance service influenced consumen decision, so that company must take focus on improving service quality. Dimension of performance services are tangibles, reliability, responsiveness, assurance, and emphathy.